Constituintes de Sorocea bomplandii Baillon - De Andrade, F. D P [UNESP]; Vilegas, Wagner [UNESP] (My University, 1998)
The chemical investigation of the leaves of Sorocea bomplandii Baillon (Moraceae) led to the identification of pentacyclic triterpenes, fatty acid ester and isoprenoids. Chromatographyc comparison between the infusion S. bomplandii with that of Maytenus aquifolium - a Celastraceae with proved antiulcer activity - has shown that they have different compositions: the first one is based on sugars and the last one is based on flavonoid glycosides.
Constituents from Sorocea bomplendii Baillon
Keywords: Moraceae; Pentacyclic triter penes; Sorocea bomplandii Baillon; antiulcer agent; fatty acid ester; flavonoid glycoside; isoprenoid; plant extract; sorocea bomplandii extract; sugar; triterpene derivative; unclassified drug; chromatography; drug activity; drug discrimination; drug identification; drug infusion; drug research; nonhuman; plant leaf